2012
DOI: 10.1371/journal.pone.0049069
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fluoxetine on Decompression Sickness in Mice

Abstract: Massive bubble formation after diving can lead to decompression sickness (DCS) that can result in central nervous system disorders or even death. Bubbles alter the vascular endothelium and activate blood cells and inflammatory pathways, leading to a systemic pathophysiological process that promotes ischemic damage. Fluoxetine, a well-known antidepressant, is recognized as having anti-inflammatory properties at the systemic level, as well as in the setting of cerebral ischemia. We report a beneficial clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
4
20
1
Order By: Relevance
“…Specifically, either FLU or DES treatments has shown to decrease the serum level of IL-1β (refs 73 , 74 , 75 , 76 , 77 ) and IL-6. 78 , 79 , 80 , 81 , 82 To the best of our knowledge, our results are the first to show anti-inflammatory effect of MPH and especially, the effect of the combined treatment of DES+MPH. However, there is a need for more studies to establish the exact mechanisms that are responsible for the immunoregulatory effects of chronic use of both antidepressants and MPH.…”
Section: Discussionsupporting
confidence: 51%
“…Specifically, either FLU or DES treatments has shown to decrease the serum level of IL-1β (refs 73 , 74 , 75 , 76 , 77 ) and IL-6. 78 , 79 , 80 , 81 , 82 To the best of our knowledge, our results are the first to show anti-inflammatory effect of MPH and especially, the effect of the combined treatment of DES+MPH. However, there is a need for more studies to establish the exact mechanisms that are responsible for the immunoregulatory effects of chronic use of both antidepressants and MPH.…”
Section: Discussionsupporting
confidence: 51%
“…We wondered whether depressive-like behaviour might be dependent on nociceptive changes elicited by CFA in mice. There is a series of previous publications demonstrating that antidepressant drugs can display analgesic effects in different inflammation models, and some of them also show anti-inflammatory effects [21,48,49]. However, in the present study, we decided to evaluate dipyrone – considering its inability to interfere with inflammation; we also evaluated pregabalin – that represents a modern pharmacological alternative for treating chronic pain, even in mood-related situations, such as fibromyalgia [50].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine (50 mg/kg) was administered by gavage to experimental animals as an oral solution (Prozac™ 20 mg/5 ml, oral solution bottle of fluoxetine hydrochloride, Lilly Laboratories, France) 18 h before hyperbaric exposure, while the wild type control group (WT cont ) received a similar saccharine fluoxetine-free solution (7.4 g/kg). This high dose of fluoxetine was determined on the basis of previous results from a mouse model of ischemia (Jin et al, 2009 ; Blatteau et al, 2012 ; Taguchi et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…When used in a single high dose, fluoxetine is also believed to mediate neuroprotection (Pariente et al, 2001 ; Chollet et al, 2011 ; Taguchi et al, 2012 ) by inhibiting NMDA-R (Vizi et al, 2013 ), regulating inflammatory effects (Kubera et al, 2001 ; Jin et al, 2009 ; Lim et al, 2009 ) and algesia (Kostadinov et al, 2014 ). We have previously demonstrated that WT mice treated with fluoxetine are more resistant to DCS and that fluoxetine inhibits the inflammatory process by reducing the level of circulating IL-6, a pro-inflammatory cytokine (Blatteau et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%